CONTENT ANALYSIS OF INFOGRAPHIC RUBRIC IN REPUBLIKA.CO.ID MEDIA - Dyah Wahyuningsih; Abdul Basit (International Research of Multidisciplinary Analysis, 2023)
Information technology and telecommunications have become a trend in every individual's life, marked by increased internet users in society. The growth in internet use has also changed the journalistic process to digitization, one of which is Republika. RepublikaÂ became the first mass media to launch an online news portal and present multiplatform information, including the power of text, graphics, audio, and visuals . One of the innovations in presenting the information presented is infographics. In this study, researchers will use content analysis with a quantitative approach by systematically identifying visible communications (manifests) in Republika.co.id infographics during May 2023. The research concludes that the infographic production of Republika co.id media in May 2023 contained 69 Infographics dominated by sports themes amounted to 15 (30%), while only 9 (13%) had religious themes. Based on the characteristic representation , republica infographics are dominated by the informational type, amounting to 44 (63.8%) and at least the mixed chart type , amounting to 2 (2.9%). Based on characteristics , all infographics produced by Republika media (100%) are static infographics. Based on the contents of the infographic, it shows that Republika adheres to the ideology of prophetic journalism by disseminating information and news using friendly, polite, peaceful, soothing and dialogic language